Acclimation of Dipterygium glaucum Decne. Grown in the Western Coastal part of Saudi Arabia to different water supplies - Sanaa A.I. Moussa; Wafaa K. Taia; Faykah G.M.Al-Ghamdy (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
The perennial shrub species Dipterygium glaucum is a dominant species in shrubby, sandy communities in Saudi Arabia. This species suffers from the severe aridity. This work aims to investigate anatomical alterations as responses to variations in water relations-resulting from different water treatments to provide information on the capability of plants to adapt to the harsh conditions. Moreover, such study can also provide information on how to restore and maintain vegetation in the arid lands worldwide. Accordingly the relative growth rate (RGR), plant productivity and the internal structure of either roots ,stems and leaves by applying three irrigation treatments, 100, 200 and 400 mm year-1 for two successive seasons , from August-November, 2005 for the first season and from May-August, 2006 for the second season. The nutritional value of the plants, including the mineral ion content in shoots and roots as well as the chemical composition of treated and wild plants was obtained. The results revealed that D.glaucum accliminate with the arid harch habitat present in the studied location and to the water availabilities and stress.